Osteogenesis imperfecta: an atypical association - Mallakmir, Snehal; Lahiri, Keya; Gahlowt, Pallavi (International Journal of Research in Medical Sciences, 2017)
Osteogenesis Imperfecta (OI) also known as ‘brittle bone disease’, is a clinically heterogeneous connective tissue disorder with defect in type I collagen. The more prevalent autosomal dominant forms of OI are caused by primary defects in type I collagen, while autosomal recessive forms are caused by deficiency of proteins which interact with type I procollagen for post-translational modification and/or folding. Few cases of OI associated with atypical features have been reported. We report a case of 54 days male child of OI associated with pyloric stenosis. The case probably is a form of autosomal recessive OI with severe phenotype.